2010
DOI: 10.1021/la904836m
|View full text |Cite
|
Sign up to set email alerts
|

A QSPR Model for the Prediction of the “Fish-Tail” Temperature of CiE4/Water/Polar Hydrocarbon Oil Systems

Abstract: The fish-tail temperatures denoted as T* have been determined or collected for 85 ternary systems based on three tetraethylene glycol monoalkyl ethers C(i)E(4) (i = 6, 8, 10), water, and 43 hydrocarbon oils of various hydrophobicities. Fourteen fragrant mono- and sesquiterpenes in addition to 29 model oils, including n-alkanes, cyclohexenes, cyclohexanes, and alkylbenzenes, were investigated in order to establish a QSPR model for the prediction of T* as a function of the chemical structure of the oils. Only tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…However, the drop size measured when different oils were used indicate a predominant effect of the nature of the oil (molecular structure). Soybean oil is composed of a mixture of fatty acids with long carbon chains, with an equivalent alkane carbon number (EACN) of 18 (the EACN is the number of carbon atoms that a linear alkane would have to result in the same phase behavior) [43]. Limonene is a terpene with fewer carbon atoms than the fatty acids in soybean oil and with an EACN close to 8 [23].…”
Section: Influence Of Oil Type On the Morphology And Rheological Behamentioning
confidence: 99%
“…However, the drop size measured when different oils were used indicate a predominant effect of the nature of the oil (molecular structure). Soybean oil is composed of a mixture of fatty acids with long carbon chains, with an equivalent alkane carbon number (EACN) of 18 (the EACN is the number of carbon atoms that a linear alkane would have to result in the same phase behavior) [43]. Limonene is a terpene with fewer carbon atoms than the fatty acids in soybean oil and with an EACN close to 8 [23].…”
Section: Influence Of Oil Type On the Morphology And Rheological Behamentioning
confidence: 99%
“…The lower EACN values of cyclic oils do not come from their greater polarity as we had previously suggested. 17 It is simply due to a smaller van der Waals surface which decreases their interactions with surrounding oil molecules and increases its partition coefficient toward the interfacial film of surfactants. In the same way, it is worth comparing the EACN of p-menthane with that of the three unsaturated and aromatic derivatives (p-menth-2-ene, α-terpinene, and p-cymene) located above it in Figure 6.…”
Section: Qspr Analysis Of Eacn Values With Cosmo-rs Descriptors Of Oilsmentioning
confidence: 99%
“…On the other end, early EOR efforts in the literature had also shown that the optimal brine salinity developed for a specific brine/oil/surfactant mixture was largely related to the alkane carbon number (ACN, the number of carbons in a straight alkane chain) for normal alkanes, or so called equivalent alkane carbon number (EACN) for a mixture of hydrocarbons or non-alkyl hydrocarbons. [15][16][17][18] Downloaded by [New York University] at 01: 14 18 June 2015 The ACN concept satisfactorily characterizes the hydrophobicity of alkane-type hydrocarbons, with higher ACN compounds being more hydrophobic. For a mixture of hydrocarbons or rather complex hydrocarbons, such as crude oil, the EACN is conveniently used for surfactant formulation design purposes.…”
Section: Introductionmentioning
confidence: 99%